Estimation of heart rate and energy expenditure using a smart bracelet during different exercise intensities: A reliability and validity study - Cai, Y.; Wang, Z.; Zhang, W.; Kong, W.; Jiang, J.; Zhao, R.; Wang, D.; Feng, L.; Ni, G. (Sensors, 2022)
Background: With wrist-worn wearables becoming increasingly available, it is important to understand their reliability and validity in different conditions. The primary objective of this study was to examine the reliability and validity of the Lexin Mio smart bracelet in measuring heart rate (HR) and energy expenditure (EE) in people with different physical activity levels exercising at different intensities.